2019
DOI: 10.3390/en12203999
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Electromagnetic Variable Valve Train with a Magnetorheological Buffer

Abstract: In this paper, an electromagnetic variable valve train with a magnetorheological buffer (EMVT with MR buffer) is proposed. This system is mainly composed of an electromagnetic linear actuator (EMLA) and a magnetorheological buffer (MR buffer). The valves of an internal combustion engine are driven by the EMLA directly to open and close, which can adjust the valve lift and phase angle of the engine. At the same time, MR buffer can reduce the seat velocity of the valve and realize the seat buffer of the electrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Applications in vehicle mainly include intake and exhaust valve, electronic injection device, suspension systems, gearshift hydraulic valve, etc. [12]- [14]. In this paper, DAMT as a new direct-drive transmission form is formed by integrating an electromagnetic linear actuator with AMT.…”
Section: Built Gearshift Model Of Amt Bymentioning
confidence: 99%
“…Applications in vehicle mainly include intake and exhaust valve, electronic injection device, suspension systems, gearshift hydraulic valve, etc. [12]- [14]. In this paper, DAMT as a new direct-drive transmission form is formed by integrating an electromagnetic linear actuator with AMT.…”
Section: Built Gearshift Model Of Amt Bymentioning
confidence: 99%
“…Figure 1 shows the structure of the electromagnetic fully variable valve. 10 From the figure it can be observed that the system is composed of an EMLA, a MR buffer, and valve components. The EMLA mainly consists of outer and inner magnetic yokes, an electromagnetic coil, a coil bobbin, and seven permanent magnets.…”
Section: System Overviewmentioning
confidence: 99%
“…Simulation and experiment results showed that valve seating characteristics become stable and soft when the engine is at the speed of 5000 r/min. Guo et al 10 and Zhu et al 11 have studied a fully variable valve system that uses the magnetorheological buffer (MR buffer) to realize seat cushioning, which could minimize the seating velocity and rebound height of the valve. In the system, the electromagnetic linear actuator (EMLA) is a moving coil linear motor that the axial driving force is generated by the current-carrying coil in the permanent magnetic field to drive the valve moving.…”
Section: Introductionmentioning
confidence: 99%
“…There were eight features (X k ) in our work, as well as labels C. The dimension of X k and C were both N × 1. We calculated the score of each feature using the MATLAB(2018a) software, based on Equation (5). The score of each feature is shown in Table 3.…”
Section: Feature Selectionmentioning
confidence: 99%
“…In addition, the manufacturing costs of aeroengines are quite high, and the replacement of an engine requires large investments, in terms of both manpower and financial resources. It is, therefore, necessary to find an effective method to monitor the condition of and predict the faults in aeroengines [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%